2021
DOI: 10.1142/s0192415x21500956
|View full text |Cite
|
Sign up to set email alerts
|

11-O-Galloyl Bergenin from Corylopsis coreanas Leaves Induces Autophagy and Apoptosis in Human Osteosarcoma

Abstract: Osteosarcoma is the most common malignant bone-forming tumor, wherein most patients with high grade osteosarcomas are treated with chemotherapy. Despite this, survival for metastatic or relapsed osteosarcoma patients has remained at an overall 5-year survival rate of 20%. In particular, the extracts of Corylopsis coreana (Korean winter hazel), a cultivated woody plant in South Korea, have shown beneficial anti-inflammatory, anti-oxidative, anti-osteoclastic, and antihyperuricemic properties. Therefore, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It also activates the PI3K/Akt signaling pathway in vivo and in vitro to reduce Parkinson’s disease symptoms [ 25 ]. Recently, it was shown that bergenin is a novel galectin-3 inhibitor with potential antitumor activity [ 26 ] and inhibits HepG2 cells and decreases the expression of the Bcl-2 family of proteins [ 27 ]. In addition, bergenin increased G1 phase arrest, and reduced expression of Ki67, cycling D1, and cycling B1 in bladder cancer cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also activates the PI3K/Akt signaling pathway in vivo and in vitro to reduce Parkinson’s disease symptoms [ 25 ]. Recently, it was shown that bergenin is a novel galectin-3 inhibitor with potential antitumor activity [ 26 ] and inhibits HepG2 cells and decreases the expression of the Bcl-2 family of proteins [ 27 ]. In addition, bergenin increased G1 phase arrest, and reduced expression of Ki67, cycling D1, and cycling B1 in bladder cancer cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%